Introduction of Lean Production at Russian Enterprises: Perspectives and Problems - Sadriev, Ruslan D.; Mullakhmetov, Khanif S.; Krotkova, Ekaterina V.; Gabaidullina, Liliia A. (International Journal of Economics and Financial Issues, 2016)
In the article the problems of introduction of the lean at Russian enterprises are studied and the main reasons for these problems are defined. At the same time an attempt of the analysis of the concept of lean production from the point of view of management is made. A number of distinctive features of the lean as a concept of management is considered. The authors consider that in the Russian management the applied principles and approaches are poorly compatible to the lean philosophy which is the main obstacle for introduction of this concept. Various points of view on the reasons of problem of the lean technology introduction, the influence of the culture of management at the enterprise upon the efficiency of lean introduction are studied. The lean introduction methodology considering the features of the Russian management and the business environment is offered. It is defined that the concept of lean has to become an organic part of the general system of management of enterprises; at the same time the principles, tools and methods of the lean differently show up at each level of management. The audit necessity and sequence of all the elements of production and management system of the enterprise regarding their compliance to the lean philosophy is proved. Keywords: economical production, lean production, management, problems, principles, tools and methods, corporate culture JEL Classifications: D29, M11, M14